PENGARUH TINGKAT KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAAN KONSUMEN SICEPET EXPRES KOTA BIMA - Ahmad Ridwan; Muhajirin - - (Universitas Mahendradatta Denpasar, 2021)
Satisfying consumer needs is the dream of every company. Apart from being an important factor for the company's survival, meeting consumer needs can increase its superiority in competition. Consumers who are satisfied with the level of trust and service quality are more likely to buy back the product and reuse the service when the same needs reappear at a later date. This study aims to determine the effect of the level of trust and service quality on customer satisfaction on the fast express in the city of Bima. This study uses a quantitative approach with a survey method, while this type of research includes associative research. The population in this study are consumers who have used the fast express service of the service, the number of samples taken in this study were 100 respondents. The sample used in this study was purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis used multiple linear regression, correlation test, determination test, partial test analysis with t test and f test (simultaneous). To test the effect between variables using SPSS (Statistical Service Product Solutions) version 23.00. The results of the study based on the t test (partial) show that the level of trust has an effect on customer satisfaction, service quality has an effect on customer satisfaction, while the level of trust and service quality simultaneously affects customer satisfaction.